The release call as a diagnostic character between cryptic related species Odontophrynus cordobae and O. americanus (Anura: Cycloramphidae) - Grenat, P. R.; Martino, L. (Zootaxa, 2013)
Diploid Odontophrynus cordobae and tetraploid O. americanus are morphologically cryptic species (Martino and Sinsch 2002). These species occurs in sympatry and syntopy in the SW of the Córdoba province, Argentina (Grenat et al. 2009). At present, individuals of O. cordobae and O. americanus can be only differentiated by mean cytogenetics (Salas 2006; Rosset et al. 2006), which involves the sacrifice of the animal, and erythrometry (Grenat et al. 2009). We propose the release call as a novel character to differentiate these species. Release vocalizations are produced by male anurans as a negative response to male mating attempts. Some studies demonstrated that the release calls of several anuran species differed specifically and that temporal structure of calls could be phylogenetically informative (Brown and Littlejohn 1972; Sullivan and Lamb 1988; Sullivan and Malmos 1994; di Tada et al. 2001). In the genus Odontophrynus, only the release call of O. cordobae has been described (Grenat et al. 2012). The sonograms of O. americanus and O. occidentalis release calls were showed by Barrio (1964), but call measurements were not reported. The aims of present study are: 1) to describe the release call of Odontophrynus americanus; 2) to compare release calls of cryptic species O. cordobae and O. americanus; 3) to evaluate release calls as diagnostic character to distinguish between these species.